Improvement of crushing strength and thermal conductivity by introduction of hetero-element Al into Li4SiO4. Issue 18 (15th December 2019) - Gong, Yichao; Li, Junjie; Yang, Shenghui; Yang, Mao; Dang, Hao; Ren, Yingying; Zhang, Guojun; Lu, Tiecheng
Abstract: Investigations on the doping modification of tritium breeding materials have been becoming one of the interesting research areas in the past few years. Recently, preparation method, mechanical and physical properties and tritium release behavior of Li4+x Si1-x Alx O4 solid solution have been studied because of its potential advantages in the field of tritium breeding materials. In this paper, a facile approach was proposed to prepare Li4+x Si1-x Alx O4 pebbles with a relatively small grain. TG/DSC and XRD were conducted to investigate the formation process of Li4+x Si1-x Alx O4 . The results showed the crushing strength and thermal conductivity were obviously improved by introduction of hetero-element Al into Li4 SiO4, and the optimal x value for Li4+x Si1-x Alx O4 was 0.2 from the point of high crushing strength and thermal conductivity. This study will be expected to provide references for fabricating other solid solution tritium breeders.